(untitled) (Conference Zone, 2021)
Primary education is universally accepted as the foundation laying level of education in all nations of the world. Today, the large-scale reforms being carried out in our country to bring up a spiritually and physically harmoniously developed generation have risen to the level of state policy. It is known that primary education is the main foundation of general secondary education, and the future success of students, their comprehensive development in many respects depends on the quality of primary education. Currently, there are more than one hundred and ten thousand primary school teachers in secondary schools of the country.